Analysing the Role of Political and Economic Factors in Setting Media Agenda in Pakistan - Nasir Iqbal; Dr. Mamoona Gul (Indus Journal of Social Sciences, 2025)
The study explores the public need for orientation regarding Pakistani traditional and social media platforms. The research examines how the need for orientation functions as a moderation factor and impacts digital agenda-setting about political instability and economic uncertainty in circumstances as portrayed by Pakistani media. Survey data collection from 1,105 students from five universities in Pakistani ranked by world QS Ranking-2025 selected on random sample technique of probability sampling to investigate dependent factors of NFO like personal involvement, personal knowledge, and cognitive effort needed to respond to the media content on media agenda acceptability. ‎The results indicate that personal involvement (r = 0.336, p < 0.01) and cognitive effort (r = ‎‎0.363, p < 0.01) are strong effect amplifiers for agenda-setting that adheres to McCombs and ‎Weaver’s NFO framework. The variable of uncertainty which forms a central part of NFO did not show any statistical connection since Pakistan appears to have normalized its state of uncertainty. NFO stays active as a mechanism that affects public priorities and media visibility while managing digital fragmentation and information saturation. Research emphasizes directional communication planning from users to resolve mental obstacles while recommending innovative strategies for dealing with excessive information overload. Research that analyzes NFO in digital networks and crisis frameworks produces updated literature on agenda setting while offering operational benefits to professionals working in the field of media policymakers.‎